Microbiological Parameters In Patients With Moderate Dentition Defects After Fixed Prosthetics (Eurasian Medical Research Periodical, 2024)
Fixed prosthetic restorations, such as crowns and bridges, are widely used to rehabilitate patients with moderate dentition defects. While these restorations restore function and aesthetics, they can significantly impact the oral microbiological environment. This thesis explores the changes in microbiological parameters in patients following fixed prosthetics, focusing on biofilm dynamics, microbial composition, and the potential risks these changes pose to oral health.